2011
DOI: 10.1292/jvms.10-0256
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Radiation at 40kHz Induces Hepatic Injury in Long-Evans Cinnamon (LEC) Rats, an Animal Model for Human Wilson Disease

Abstract: ABSTRACT. In the present study, we examined effects of radiofrequency (RF) radiation at 40 kHz on hepatic injury in Long-Evans Cinnamon (LEC) rats, an animal model for human Wilson disease, which is a heritable disease of copper metabolism in the liver. The activities of ALT and AST in serum of LEC rats exposed to RF radiation for 2 weeks were approximately 3.8-fold and 2-fold higher than those in serum of sham-exposed rats, respectively. Although there were no significant differences in hepatic copper content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Mohammed Fathy Assasa [25] observed a significant increase in SGOT and SGPT following exposure of rat to EMF from cellular telephones base stations with frequency of 900 MHz. Exposure of rats to radiofrequency radiation for 2 weeks at 40 KHz increased approximately 3.8-fold and 2-fold higher SGPT and SGOT respectively [26]. Our study observations are consistent with Ma HR et al [24] study.…”
Section: Discussionsupporting
confidence: 92%
“…Mohammed Fathy Assasa [25] observed a significant increase in SGOT and SGPT following exposure of rat to EMF from cellular telephones base stations with frequency of 900 MHz. Exposure of rats to radiofrequency radiation for 2 weeks at 40 KHz increased approximately 3.8-fold and 2-fold higher SGPT and SGOT respectively [26]. Our study observations are consistent with Ma HR et al [24] study.…”
Section: Discussionsupporting
confidence: 92%
“…Although the research is sparse, EPAs operating at significantly lower RF ranges (< 1 MHz) have also been reported and used in clinical practice to induce mild hyperthermia and other physiological effects [15][16][17][18]. An example for such EPAs currently used in therapy practice is Capacitive Resistive Monopolar Radiofrequency (CRMRF) that operates at a frequency of 448 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this review identified a limited number of articles pertaining to this area. [46][47][48]50,[64][65][66][67][68][69][70][71][72][73][74][75][76][77] The current literature (published in English) indicates that the RF used in therapy-related clinical practice is predominantly in the SWT band, and largely limited to PSWT as a delivery mode. 3,9,62,[78][79][80] Although several authors have reviewed the therapeutic effects of SWT as they are applied to various specific conditions, 56,62,79,[81][82][83] none covers all the therapy-related clinical literature in this frequency spectrum.…”
Section: Introductionmentioning
confidence: 99%